Accounting Fundamentals - Charlene, Schick P., Gonzalez, Jean, Kennedy, David S; Gonzalez, Jean; Kennedy, David S; Charlene, Schick P. (New Jersey, USA : Prentice-Hall Inc, 1987)
Accounting Fundamentals provides a practical approach to the study of accounting. It is meant for the student who never intends to take another accounting course and for the student who wishes to pursue further studies in accounting.
include index
jbi, 14/03/2018
Loans
Keywords: accounting